Using the Theory of Planned Behavior to Explain and Predict Areca Nut Use Among Adolescents in India: An Exploratory Study - Gupte HA; Chatterjee N; Mandal G (Dove Medical Press, 2022)
Himanshu A Gupte,1 Nilesh Chatterjee,1 Gauri Mandal2 1Narotam Sekhsaria Foundation, Mumbai, Maharashtra, India; 2Salaam Bombay Foundation, Mumbai, Maharashtra, IndiaCorrespondence: Nilesh Chatterjee, Narotam Sekhsaria Foundation, First Floor, Nirmal Building, Nariman Point, Mumbai, 400 021, India, Tel +91-9819472736, Email nileshchatterjee100@gmail.comContext: Areca nut, used alone or in combination with tobacco, contributes to the high oral cancer burden in India. Used widely by adolescents, who perceive it as a harmless substance, areca nut is addictive and considered a precursor to tobacco use. Given its serious implications for addictiveness and physical health, urgent preventive interventions for areca nut use are required in India and South-East Asia. Studies examining the role of health behavior theory in explaining and predicting areca nut use and for development of its prevention among adolescents are scarce.Aim: This study explored the role of the components of Theory of Planned Behavior (TPB) such as attitudes, subjective norms, perceived behavioral control, and intention in predicting areca nut use among adolescents.Settings and Design: Observational study with cross-sectional design conducted with 1884 male and female adolescents attending low-income schools in Mumbai, India.Methods and Material: Self-administered surveys were used to gather data on age, gender, behavioral factors and areca nut use.Statistical Analysis Used: Chi-square and Mann Whitney test for bivariate and logistic regression for multivariate analysis.Results: Around 27.2% of 1884 participants were areca nut users. The mean age of users was 13.75 years. Intention-to-use and perceived behavioral control were statistically significant predictors of actual areca nut use (p< 0.001). The components of TPB such as attitude, perceived subjective social norms, and perceived behavioral control had a statistically significant effect on the intention-to-use areca nut (p< 0.05).Conclusion: This exploratory study indicates that constructs from TPB could help us understand and predict areca nut use. However, more rigorous future research is required to generate insights that help craft effective theory-based behavioral interventions for areca nut prevention and cessation in adolescents.Keywords: areca nut, supari, adolescents, India, theory of planned behavior